2014
DOI: 10.1093/bja/aet577
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative glucocorticoids and long-term survival and cancer recurrence after colectomy: follow-up analysis of a previous randomized controlled trial

Abstract: Preoperative dexamethasone was associated with a higher rate of distant recurrence in patients undergoing colectomy for colon cancer. Given the small sample size, this finding should be interpreted with caution, but warrants further investigation in a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 41 publications
2
46
2
2
Order By: Relevance
“…However, neither the present study nor previous meta-analyses have identified a significant negative association with either wound complications or anastomotic leak14,15 Furthermore, there have been some concerns that preoperative corticosteroids may have a negative impact on oncologic outcome following surgery for colorectal cancer; however, the evidence for this is limited in both numbers and length of follow-up 22…”
Section: Discussioncontrasting
confidence: 70%
“…However, neither the present study nor previous meta-analyses have identified a significant negative association with either wound complications or anastomotic leak14,15 Furthermore, there have been some concerns that preoperative corticosteroids may have a negative impact on oncologic outcome following surgery for colorectal cancer; however, the evidence for this is limited in both numbers and length of follow-up 22…”
Section: Discussioncontrasting
confidence: 70%
“…Indeed, recent meta-analysis of both experimental and clinical trials suggests that receiving corticosteroids at standard therapeutic doses for 10 days or less is unlikely to impair wound healing [56]. Lastly, as recent preliminary reports suggest that preoperative corticosteroids may have a detrimental impact on oncologic outcome, some consideration should be given to their impact on longer term outcomes, especially in surgery for gastrointestinal cancer [57][58].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who had received a dose of dexamethasone (8 mg) had a significantly higher rate of distant recurrence compared with those who received placebo (six patients in the dexamethasone group vs one patient in the placebo group; P = 0.04) and a non-significant trend towards higher cancer-specific mortality. 66 …”
Section: Dexamethasonementioning
confidence: 99%